Seismic Analysis Of Irregular Reinforced Concrete Building - Hassan, Nur Munira (Universiti Sains Malaysia, 2017)
Most buildings in Malaysia are not designed with earthquake loading though threat of an active earthquake from Indonesia is real. The purpose of this project is to study the effect of irregularity using static and dynamic analysis along with the seismic performance of irregular reinforced concrete frame in 3D analysis using STERA 3D. Nonlinear static pushover (POA) and Incremental Dynamic Analysis (IDA) were run on the frames. The POA will be focusing on drift-shear relation and capacity curve of the building whereas the IDA will utilise incremental dynamic analysis (IDA) curve. There are three vertically irregular frame with different number of stories which are 3, 6 and 9. For IDA the frame were subjected to seven different type of ground motion which are Chalfant Valley (July 1986), Coalinga (July 1983), Imperial Valley (October 1979), Kobe (January 1995), Mammoth Lake (May 1980), Ranau (June 2015) and Whittier Narrow (October 1987) with increment of its magnitude by 0.2g, 0.4g, 0.6g, 0.8g, and 1.0g, respectively. The result obtained from POA for capacity curve shows that the 3, 6 and 9 story frames had undergone building collapse after nearing the collapse limit state and the low rise building has the highest resistance towards the ground motions while the drift-shear relation curve shows that the story displacement for first floor is the highest in every story and the value increases with the number story. In IDA the result shows that Imperial Valley has the highest displacement for 9 story while Ranau has the lowest value of displacement for 9 story and the ground motion with higher peak ground acceleration (PGA) value will caused an increase in the displacement value.